Adolescent and young adult tobacco prevention and cessation: current status and future directions. (26th November 2003) - Backinger, C L; Fagan, P; Matthews, E; Grana, R
Abstract : Objective: To summarise the evidence on adolescent and young adult prevention and cessation, and provide future directions for research. Data sources: Data were collected from published literature. Searches for adolescent prevention were conducted using PubMed, PsycInfo, and ERIC; and for cessation, PubMed, and two major reviews that span January 1978 to May 2002. PubMed, PsychInfo, and SCCI were searched for young adults from January 1990 to May 2002. Study selection: Data included smoking prevention studies published from January 1990 to May 2002 and conducted in the USA; all identified smoking cessation studies for adolescents. Young adult data were limited to initiation and cessation studies. Data extraction: Extraction of data was by consensus of the authors. Data synthesis: Results of the review are qualitative in nature using a consensus approach of the authors. Conclusions: School based curricula alone have been generally ineffective in the long term in preventing adolescents from initiating tobacco use but are effective when combined with other approaches such as media and smoke-free policies. Prevention research should consider multiple approaches and the social conditions that influence the development of youth problem behaviours including tobacco use. Because youth smoking cessation has been understudied to date, scientifically rigorous adolescent smoking cessation studies need to be conducted with attention to high risk smokers and less than daily smokers. Tobacco prevention and cessation for young adults needs focused attention. Prevention and cessation programmes need to address other tobacco products in addition to cigarettes.